Fatigue characteristics of modified asphalt binders using fracture mechanics. (March 2016) - Nuñez, Javier Yesid Mahecha; Leonel, Edson Denner; Faxina, Adalberto Leandro
Abstract: This paper presents a new criterion to estimate fatigue characteristics of modified asphalt binders based on fracture mechanics theory. A finite element analysis using the FRANC2D software was carried out to establish the relationship between the crack length propagation and the stress intensity factor of the specimen tested in the Dynamic Shear Rheometer. The experimental results showed that temperature rise reduces two fracture parameters: crack growth rate at failure ( da / dN ) and stress intensity factor (Δ K ). da / dN and Δ K showed high capacity of explaining the fatigue characteristics of modified asphalt binders. Modifiers may improve mechanical damage resistance of the asphalt binder.